Geographical Indications- a marketing strategy tool for small farms in Albania - Mece, Manuela (European Journal of Multidisciplinary Studies, 2023)
GIs offer a unique marketing tool for producers, differentiating their products from generic counterparts, and can enhance the market position of producers by capitalizing on the reputation and distinctiveness associated with a specific geographic region. Geographical Indication (GI) can be used as a strategy for marketing the product and the territory. It creates synergy with the preservation of cultural heritage; with consumers’ value attributed to the specific qualities of that product; with the economic development and the livelihoods of rural communities. Balkan Countries are making serious efforts for creating their competitive advantage whereas Albania is still in the initial steps. One product that is expected to create synergy with the Tourism industry as a potential GI in Albania is the Winery sector.